KEMASAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI BANDUNG SERTA TANTANGAN PENYELAMATAN LINGKUNGAN - Wijayakusuma, Ita Hanami; Apresian, Stanislaus Risadi; Pakpahan, Aknolt Kristian (Media Riset Bisnis & Manajemen, 2025)
This research aims to review the reasons why micro, small, and medium enterprises (MSMEs) in Bandung use non-environmentally friendly packaging using a qualitative research method with a multiple case study design by looking at the sustainability practices of six MSMEs located in Bandung, namely Oei Baked, Kojju Cake, Fiorina Wear, Socks Em All, Gurumikoe, and The Journails. The main focus of the study is the implementation of a green economy which is a challenge for MSMEs in Bandung related to the use of packaging. Data were collected through asynchronous interviews covering questions such as packaging use, advantages and disadvantages of the packaging used, and future commitments regarding environmentally friendly packaging. The results show that the majority of MSMEs still face challenges in implementing green economy practices related to environmentally friendly packaging. MSMEs in Bandung have made a future commitment to using environmentally friendly packaging. The study provides recommendations for environmentally friendly packaging and socialization from the Bandung City government so that all MSMEs can implement a green economy